Effects of culinary treatments on the lipid nutritional quality of fish and shellfish - Karsoon Tan; Leiheng Huang; Kianann Tan; Lim, Leong Seng; Ya Peng; Cheong, Kit-Leong (Elsevier Ltd., 2023)
Coronary heart disease (CHD) is one of the leading causes of death worldwide. Seafood, especially fish and shellfish, is a healthy food that reduces the risk of CHD. In many regions, seafood is consumed cooked to eliminate potentially pathogenic microorganisms. Although there have been many reports of culinary preparations causing changes in the fatty acid profile of fish and shellfish, this information has not been well organized, and most of it is not associated to CHD. Therefore, this study was conducted to study the effect of culinary treatments of seafood on lipid nutritional quality in relation to promotion/prevention of CHD. In this study, fatty acid profiles of fish and shellfish prepared with different culinary preparations were obtained from published literature. Lipid nutritional quality indices related to promoting/preventing CHD were calculated and analyzed to reveal the effects of culinary treatment on the lipid nutritional quality of fish and shellfish in promoting/preventing of CHD. The information in this article is very useful and can fill the knowledge gap of the effects of culinary preparation on the lipid nutritional quality of fish and shellfish. Such information is very useful for guiding consumers to choose better ways to cook fish and shellfish to reduce the risk of CHD.